(untitled) (Raparin Journal of Humanities (RJH), 2024)
Hussein son of Ali’s movement is one of the most interesting events of the Umayyad era that attracts the attention of many historians, especially because he was martyred as a result of this movement in the year 61 A.D., which It is worth noting that some historians have exceeding the recording of the events of this movement in narrating some phenomena and events after the revolution that are far from the truth, which is due to the sympathy of the historian’s supporters and the influence of the political side. In writing history in the later Abbasid era, except for the critical deficiencies in recording history in this era, this research shows all the excesses in the event with the cause of excess, and at the same time the response and attention of some later historians on the excesses of this event.